Development of a simulator of the SIMBIOSYS suite onboard the BepiColombo mission. Issue 2 (31st October 2019) - Slemer, A; Zusi, M; Simioni, E; Da Deppo, V; Re, C; Lucchetti, A; Della Corte, V; Filacchione, G; Palumbo, P; Capaccioni, F; Capria, M T; Amoroso, M; et al.
ABSTRACT: BepiColombo is the fifth cornerstone mission of the European Space Agency (ESA) dedicated to study the Mercury planet. The BepiColombo spacecraft comprises two science modules: the Mercury Planetary Orbiter (MPO) realized by ESA and the Mercury Magnetospheric Orbiter provided by the Japan Aerospace Exploration Agency. The MPO is composed by 11 instruments, including the 'Spectrometer and Imagers for MPO BepiColombo Integrated Observatory System' (SIMBIOSYS). The SIMBIOSYS suite includes three optical channels: a Stereoscopic Imaging Channel, a High Resolution Imaging Channel, and a Visible and near Infrared Hyperspectral Imager. SIMBIOSYS will characterize the hermean surface in terms of surface morphology, volcanism, global tectonics, and chemical composition. The aim of this work is to describe a tool for the radiometric response prediction of the three SIMBIOSYS channels. Given the spectral properties of the surface, the instrument characteristics, and the geometrical conditions of the observation, the realized SIMBIOSYS simulator is capable of estimating the expected signal and integration times for the entire mission lifetime. In the simulator the spectral radiance entering the instrument optical apertures has been modelled using a Hapke reflectance model implementing the parameters expected for the hermean surface. The instrument performances are simulated by means of calibrated optical and detectors responses. The simulator employs the SPICE (Spacecraft, Planet, Instrument, C-matrix, Environment) toolkit software, which allows us to know for each epoch the exact position of the MPO with respect to the planet surface and the Sun.